SEKSUAL DAN HARMONISASI RUMAH TANGGA DALAM LONTAR RAHASYA SANGGAMA - Brahmandika, Pande Gede (Kalangwan Jurnal Pendidikan Agama, Bahasa dan Sastra, 2024)
This study examines the sexual and household harmony teachings contained in the Lontar Rahasya Sangama, an ancient text in the Balinese literary tradition. This lontar provides ethical and spiritual guidance on how husband and wife relationships can be built and maintained based on a balance between physical and spiritual aspects. Through a qualitative approach with descriptive-analytical methods, this study reveals the symbolic meaning and values ​​contained in the teachings, as well as their relevance in modern household life. The results show that Rahasya Sangama not only emphasizes the importance of sexual relations as a form of fulfilling biological needs, but also as a means to achieve harmony in family life. Husband and wife relationships are seen as a form of yoga or union that reflects the balance between masculine and feminine elements in the universe. This study also found that the teachings in Rahasya Sangama have strong relevance in the context of modern life, especially in efforts to maintain household stability and well-being amidst rapid social change. Thus, this study contributes to a deeper understanding of how Balinese cultural and spiritual values ​​can be applied in everyday life, as well as providing insight into the importance of preserving local wisdom in facing the challenges of globalization. Keywoard: Rahasya Sanggama Palm Leaf, Sexuality, Household Harmony, Balinese Culture